Problems and Trends in Promoting Japanese Automotive Products on World Markets - I. V. Makarova; D. Z. Nikolishvili (Мир новой экономики, 2021)
This paper presents a study of the international car market; analysis of the development of automotive markets in Europe and Russia’s national car market; a review of the global car market; and international trading activity in the car market. Japan’s automotive industry is signifiantly developed with Toyota as one of the world’s leaders. Also, in addition to cars, Japanese companies are among the leaders in the production of motorcycles and engines for cars participating in sports races. Japanese legislation encourages the production and sale of cars with high environmental friendliness, hybrid and electric cars. This step allows companies to focus their production on a new class of cars, which helps Japanese companies outstrip European and American cars of the future. However, cars’ air pollution is relevant for Japan since the state subsidizes automakers and consumers, reducing taxes and supporting companies that switch to hybrid vehicles.